Recent development of micro-nano carriers for oral antineoplastic drug delivery - Hongzheng Li; Xiang Chen; Shangrui Rao; Minyu Zhou; Jianhua Lu; Danna Liang; Bingzi Zhu; Letian Meng; Ji Lin; Xiaoya Ding; Qingfei Zhang; Danhong Hu (Materials Today Bio)
Chemotherapy is widely recognized as a highly efficacious modality for cancer treatment, involving the administration of chemotherapeutic agents to target and eradicate tumor cells. Currently, oral administration stands as the prevailing and widely utilized method of delivering chemotherapy drugs. However, the majority of anti-tumor medications exhibit limited solubility and permeability, and poor stability in harsh gastrointestinal environments, thereby impeding their therapeutic efficacy for chemotherapy. Therefore, more and more micro-nano drug delivery carriers have been developed and used to effectively deliver anti-cancer drugs, which can overcome physiological barriers, facilitate oral administration, and ultimately improve drug efficacy. In this paper, we first discuss the effects of various biological barriers on micro-nano drug carriers and oral administration approach. Then, the development of micro-nano drug carriers based on various biomedical components, such as micelles, dendrimers, hydrogels, liposomes, inorganic nanoparticles, etc. were introduced. Finally, the current dilemma and the potential of oral drug delivery for clinical treatment were discussed. The primary objective of this review is to introduce various oral delivery methods and serve as a point of reference for the advancement of novel oral delivery carriers, with the ultimate goal of informing the development of future clinical applications.